THE INVESTIGATION OF CROSS-CULTURE ADJUSTMENT OF EXPATRIATE IN SEMARANG (Based on the DMIS Stage by Milton J. Bennett) Bintang Mahardhika Naratri, Mirwan Surya Perdhana - Naratri, Bintang Mahardhika; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to analyze the barrier of cross-cultural adjustment ability of expatriates in Indonesia, with demographic factors such as gender and age.This study uses a qualitative method by collecting data with interview to get deeper information about the cross-cultural adjustment process of expatriate while in Indonesia. The participant used in the form of female respondents with Japanese citizenship who have spent 10 years in Indonesia, and applying Milton J. Bennett's Theory of Developmental Model of Intercultural Sensitivity.The results of this study indicate that some of the barriers to the cross cultural adjustment process are the use of language at an early stage, the level of privacy at the time of socialization, and also the time management of Indonesian people.